Bayesian machine learning identifies precipitation as a key predictor in alpine soil carbon spatial structuring - Zhaoqi Wang; Sheng Yu; Xiaotao Huang; Ting Zhou; Haichen Zhang; Yangyang Liu; Guiling Wu; Kai Zheng; Mingxue Xiang; Tao Ma; Dan Liu; Yongkang Lu (Soil and Tillage Research, 2026)

Synthesis of high-density polycycloalkanes fuel via Ru/TiO2 catalysts: modulating strong metal-support interaction - Guangya Feng; Guiling Wu; Guoqing Sun; Lili Tian; Wenli Zhao; Xiangwen Zhang; Qingfa Wang (Fuel, 2026)

The study of intestinal toxicity induced by gossypol acetic acid and the mechanism using zebrafish model and network toxicology - Hanxue Zhao; Yuxin Wang; Guoliang Zhang; Yudi Jing; Fangzhen Li; Xiqiang Chen; Kechun Liu; Guiling Chen; Rongchun Wang (Toxicology and Applied Pharmacology, 2026)

Rapid biodegradation of glyphosate by plant growth-promoting Ochrobactrum sp. Y3: Degradation kinetics, metabolic pathways and environmental bioremediation - Shichen Dai; Chenxi Yan; Mingqiu Liu; Yuxi Sun; Keyi Wang; Guiling Si; Mohamed A. Ghorab; Shaohua Chen (Journal of Environmental Chemical Engineering, 2026)

Chronic exposure to environmentally relevant diazepam alters behaviour, gut microbiome, and offspring phenotype in zebrafish (Danio rerio) - Ting Xu; Yilin Huang; Guiling Yang; Wenqin Tu; Ting Luo; Dou Wang; Yuanxiang Jin (Environmental Pollution, 2026)

Lithium enrichment in geothermal systems of the Tibetan Plateau: A coupled machine learning–geochemistry framework for mechanism and prediction - Shuaichao Wei; Wei Zhang; Guiling Wang; Feng Liu; Feng Tian; Xiaoxue Yan; Ruoxi Yuan; Zengrun Yang; Yong Fu (Earth-Science Reviews, 2026)

Unveiling the dominant role of LiOH in interfacial degradation: A quantitative strategy for tailored surface coating on Ni-rich cathodes - Fushui Zhou; Ruijie Wang; Wenhui Wang; Yuxuan Zhang; Guiling Yang (Chemical Engineering Journal, 2026)

A Synergistic Botanical Compound Preparation of Ganoderma lucidum, Lycium ruthenicum, and Red Ginseng Alleviates Exercise-Induced Fatigue via Coordinated Regulation of Energy Metabolism, Oxidative Stress, and Gut Microbiota in Mice - Tao Liu; Mengmin Li; Wanyun Xu; Zhenhao Li; Yuanxiang Jin; Ting Luo; Tao Ma; Jintao Cheng; Shiyu Li; Qingchi Wang; Kan Shao; Yi Yang; et al. (Food Bioscience, 2026)

Optimizing geothermal reservoir performance: A hybrid DFN-EPM simulation approach for fracture convection equivalence and enhanced production forecasting - Honglei Shi; Chuan Lu; Kefei Sun; Guiling Wang; Yaning Wang; Lu Liu; Jun Gao; Yunjie Wei (Geothermics, 2026)

Ultrasensitive and selective detection of metronidazole residues in milk powder using a novel 3D MOF fluorescent sensor - Xuanqi Zhang; Guiling Gao; Xiaoyong Lai; Qin Hou; Yi Li; Zhiyong Teng; Xiaozhong Wang; Xiao Zhang; Qingfeng Yang (Food Chemistry, 2026)

Soil Li-Rb-Cs-B as near-surface tracers of shallow-buried high-temperature geothermal systems: A case study from the Yangbajing geothermal field, Tibet Plateau - Wanli Wang; Guiling Wang; Yajuan Duan; Linxiao Xing; Wei Zhang; Jiayi Zhao; Honglei Shi; Lu Liu; Yanliang Tian; Sonam Tsering (Geothermics, 2026)

Characterization of geothermal water-rock interaction processes and transport patterns using geochemical methods - Zhang Hanxiong; Wang Guiling; Zhang Wei; Wang Mengmeng (Geochemistry, 2026)

Covalently bonded amino-functionalized ZIF-8 on Cu2O for photocatalytic reduction of low-concentration CO2 - Jinke Li; Zhenbo Zhang; Guiling Liu; Hao Shi; Jingru Wang; Jiayi Wan; Tong Bian; Huijun Yu (Chemical Engineering Journal, 2026)

Optimization of coal-based solid fuels for direct carbon fuel cells by chemical treatments - Yue Ding; Xuan Zhang; Shuyue Liu; Jinling Yin; Xianchao Wang; Jing Zhao; Qing Wen; Jiaxin Yao; Guiling Wang (Fuel, 2026)

Multiple-level fault controlled hydrothermal system in Huangshadong, Southeast China: Insights from coupled geophysical and geochemical investigations - Lu Liu; Xianan Qin; Zheng’an Wei; Min Zhang; Honglei Shi; Xiting Long; Wenjing Lin; Mingxiang Qiu; Guiling Wang; Shihua Qi; Fei Liu (Geothermics, 2026)

Machine learning for fault-controlled geothermal systems exploration in Chenzhou and Huizhou region, Southeast China - Yuzhong Liao; Guiling Wang; Wei Zhang; Hanxiong Zhang; Jiyun Liang; Yufei Xi (Geothermics, 2026)

Secukinumab improves pregnancy outcomes in recurrent spontaneous abortion with T helper 17 cells/T regulatory cells imbalance: a retrospective cohort study - Guihua Zhu; Xue Wang; Shuqin Bi; Juan Liu; Guiling Yuan; Ning Li; Jinhua Fu; Long Zhao (European Journal of Clinical Pharmacology, 2026)

Shaking table test on the seismic response of a multifloored grain warehouse structure considering the soil–structure interaction effect - Zhang Yanan; Xu Qikeng; Huang Yilin; Ding Yonggang; Wang Guiling (Soil Dynamics and Earthquake Engineering, 2025)

Research on the mechanism of acidizing the carbonate Gaoyuzhuang Reservoir, North China: Insights from field experiments and numerical simulations - Gaofan Yue; Guiling Wang; Feng Ma; Xi Zhu; Xiaoyuan Li (Geothermics, 2025)

Recombinant PD1 liposome loading nintedanib for pulmonary fibrosis therapy in mice - Qian Luo; Ying Xie; Jiarui Xu; Yuxin Ren; Shuyuan Xiong; Hongrui Zhang; Yuling Chen; Haocheng Chen; Jinling Wang; Pengyu Huang; Liyu Sun; Peishan Li; et al. (Chemical Engineering Journal, 2025)

Global immunostimulatory mechanisms of a high-branched glycogen from Glyptocidaris crenularis eggs in RAW264.7 macrophages via BONCAT-based nascent proteomics - Qingchi Wang; Yuhang Luo; Yi Xin; Yuanxiang Jin; Guiling Yang; Quanbin Zhang; Zhengshun Wen (Carbohydrate Polymers, 2025)

Fibroblast Growth Factor 8 Suppresses Neurotoxic Astrocytes and Alleviates Neuropathic Pain via Spinal FGFR3 Signaling - Huizhu Liu; Lanxing Yi; Guiling Li; Kangli Wang; Hongsheng Wang; Yuqiu Zhang; Benlong Liu (Neuroscience Bulletin, 2025)
Astrocytes in the spinal dorsal horn (SDH) exhibit diverse reactive phenotypes under neuropathic conditions, yet the mechanisms driving this diversity and its implications in chronic pain remain unclear. Here, we report that spared nerve injury (SNI) induces marked upregulation of both complement component 3 (C3⁺, A1-like) and S100 calcium-binding protein A10 (S100A10⁺, A2-like) astrocyte subpopulations in the SDH, with elevated microglial cytokines including interleukin-1α, tumor necrosis factor-α, and complement component 1q. Transcriptomic, immunohistochemical, and Western blot analyses reveal co-activation of multiple reactive astrocyte states over a unidirectional shift toward an A1-like phenotype. Fibroblast growth factor 8 (FGF8), a neuroprotective factor via FGFR3, mitigated microglia-induced C3⁺ astrocyte reactivity in vitro and suppressed spinal C3 expression and mechanical allodynia following intrathecal administration in SNI mice. These findings reveal a microglia–astrocyte signaling axis that promotes A1 reactivity and position FGF8 as a promising therapeutic candidate for neuropathic pain by modulating astrocyte heterogeneity.

Study on the pore structure evolution of granodiorite after cyclic thermal shock - Shutao Zhou; Qiang Sun; Guiling Wang; Xiting Long; Jianjun Hu; Tingxin Li (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Enhancing geothermal energy recovery in Yangbajing: The role of natural and artificial fracture connectivity in EGS performance - Honglei Shi; Guiling Wang; Chuan Lu; Wanli Wang; Lu Liu; Yunjie Wei (Geothermics, 2025)

A SERS-active microneedle array for rapid and minimally invasive lactic acid detection - Xinyu Sun; Kequan Chen; Yang Wang; Zhiwei Zhang; Jinfeng Lin; Guiling Liu; Dianhuai Meng; Jian Dong; Yan Huang (Analytica Chimica Acta, 2025)

Responses of June Precipitation in Eastern China to Late Spring Soil Temperature Anomaly over the Qinghai–Xizang Plateau: Results from a Regional Climate Model - Wenchao Wang; Miao Yu; Yongkang Xue; Jianping Tang; Weiguang Liu; Guiling Wang; Jie Zhang; Hong Wu (Journal of Meteorological Research, 2025)

An SNP for the splice donor variant of i-type lysozyme 2 (lyz-i2) is associated with the resistance of Vibrio harveyi in Pacific white shrimp - Xin Zhang; Peng Luo; Chunhua Ren; Pengying Li; Yehui Tan; Hao Yang; Shuyang Wen; Bo Ma; Jiayue Yin; Yanhong Wang; Xiao Jiang; Jingxuan Liang; et al. (Aquaculture, 2025)

An improved modeling method using overlapping meshes for geothermal wellbore simulation - Peng Hong; Fuyan Zhao; Haiyan Lei; Guiling Wang; Chuanshan Dai (Geothermics, 2025)

3-Phenoxybenzoic Acid Induces Neuronal Pentraxin 2 to Upregulate Complement Activity and Promotes Microglia-Mediated Neuronal Synaptic Damage - Guiling Hu; Kaidong Wang; Chenyang Wu; Qi Liu; Qianrong Zhang; Ai Qi; Min Huang (Journal of Molecular Neuroscience, 2025)

Petrological and geochemical insights into the genesis and geothermal potential of Late Neoarchean granitoid rocks in the Matouying Uplift, North China Craton - Quan Gan; Luming Song; Shuantong Shangguan; Xiaofei Qi; Zhiwei Liao; Jianye Chen; Zhili Yang; Guiling Wang; Guangyao Xin; Chongyuan Zhang (Precambrian Research, 2025)

3D porous carbon materials in situ-embedded with Fe3C/Fe nanoparticles as high-performance anode electrocatalysts of microbial fuel cells - Shaochuan Wang; Dongsheng Zhao; Zhenghui Qiu; Guiling Zhang; Cunguo Lin (Journal of Environmental Chemical Engineering, 2025)

Accordion-structured robust zinc anodes via MXene-guided deposition towards durable zinc-ion batteries - Yiyang Mao; Zhuo Li; Qidi Zhang; Qi Fan; Yuao Wang; Jing Zhao; Guiling Wang; Dianxue Cao; Kun Liang; Kai Zhu (Chemical Engineering Journal, 2025)

A UAV attitude fusion algorithm based on gradient descent-improved EKF - Guiling Zhao; Yuan Wang; Weidong Liang; Hongxing Zhao (Earth Science Informatics, 2025)

Error compensation method of GNSS/INS integrated navigation system based on PSO-LSTM - Guiling Zhao; Yuan Wang; Xu Wang (Advances in Space Research, 2025)

Genetically engineered Bacillus subtilis-derived extracellular vesicles Alleviates Ulcerative colitis by restoring intestinal barrier and regulating gut microbiota - Jiali Chen; Chaozhi Wei; Chunqiang Pan; You Wei; Baoxian Li; Tao Liu; Xiao Wang; Zhengshun Wen; Yao Zhao; Mengyu Zhang; Jintao Cheng; Yuanxiang Jin; et al. (Chemical Engineering Journal, 2025)

Resource utilization of red mud with biochar to prepare high-efficiency denitration catalysts - Bo Song; Zhenxing Shen; Zitong Wang; Guiling Zhou; Qin Peng; Hao Fan; Jia Liu (Journal of Cleaner Production, 2025)

Identification of male-specific molecular markers under the low-quality and non-chromosome-level genome revalidated the male heterogamety in bullfrog Aquarara catesbeiana - Yanzhe Wang; Guodong Wang; Lili Zhang; Jingyan Tang; Ling Wang; Chunxiao Zhang; Guiling Zhang; Hui Ge (Aquaculture International, 2025)

Constraints of hydrochemical and geological controls in deep-circulation geothermal systems: Insights from Chengde, Dehua, and Tashkorgan geothermal fields in China - Xiao Wang; Guiling Wang; Haonan Gan; Yu Zhang; Zhijuan Gao (Geothermics, 2025)

Role of Natural Discontinuities in Fracture Propagation in Hot Dry Rock: Observations and Implications from the Field Injection Test - Jingyu Xie; Zhengguang Zhao; Lei Li; Hao Zhang; Jing Zheng; Wei Qiao; Chongyuan Zhang; Suping Peng; Guiling Wang; Dan Wang; Xianpeng Jin (Rock Mechanics and Rock Engineering, 2025)

Regulation and response of heterotrophic bacterial production to environmental changes in marginal seas of the Western Pacific Ocean - Qiao Liu; Jinyan Wang; Xiao-Jun Li; Ni Meng; Gui-Peng Yang; Guiling Zhang; Guang-Chao Zhuang (Global and Planetary Change, 2025)

A robust SVD-UKF algorithm and its application in integrated navigation systems - Guiling Zhao; Zihao Jiang; Jinbao Wang; Shuai Gao (Advances in Space Research, 2025)

Effects of light intensity and light duration on growth performance and ovarian development in red swamp crayfish Procambarus clarkii (Girard, 1852) - Long Wang; Meng Hu; Lin Cai; Yurui Wang; Tianyu Guan; Chuankun Zhu; Hui Wang; Guiling Wang; Jiale Li (Aquaculture International, 2025)

Refining water and carbon fluxes modeling in terrestrial ecosystems via plant hydraulics integration - Shanshan Sun; Lingcheng Li; Zong-Liang Yang; Guiling Wang; Nate G. McDowell; Ashley M. Matheny; Jian Wu; Shiqin Xu; Hui Zheng; Miao Yu; Dagang Wang (Agricultural and Forest Meteorology, 2024)

A genome-wide association study and an accurate genotyping strategy to identify and validate the SNPs related to the larval period in bullfrog Aquarana catesbeiana - Yanzhe Wang; Guodong Wang; Lili Zhang; Wencheng Xu; Guiling Zhang; Hui Ge (Aquaculture International, 2024)

A lattice Boltzmann flux solver with the 1D-link interpolation scheme for simulating fluid flow and heat transfer in fractured porous media - Fuyan Zhao; Peng Hong; Chuanshan Dai; Guiling Wang; Haiyan Lei (Computers & Geosciences, 2024)

Comparison of resting-state brain activity between insomnia and generalized anxiety disorder: A coordinate-based meta-analysis - Tongfei Jiang; Xuejiao Yin; Liying Zhu; Guiling Wang; Fan Zhang; Jing Guo (Brain Imaging and Behavior, 2024)

Hydrogeochemistry of geothermal water in Huangshadong and adjacent areas of Guangdong province: Implications for water-rock interaction - Lu Liu; Guiling Wang; Yalu Li; Zhengan Wei; Wenjing Lin; Xianan Qin; Min Zhang; Shihua Qi; Xiting Long (Geothermics, 2024)

Exploring the dynamic behaviors of five pesticides in lettuce: Implications for consumer health through field and modeling experiments - Yanhua Wang; Panpan Liu; Guiling Yang; Fang Shu; Chen Chen (Food Chemistry, 2024)

Spatiotemporal modulation of immune microenvironment via composite hydrogel brakes for diabetic wound healing - Jiaying Yang; Mengyu Lai; Yuhang Ma; Jingzhu Wu; Chuan Zhang; Huiwen Yuan; Guiling Liang; Chuchen Meng; Yanmei Su; Bing Luan; Liping Gu; Yufan Wang (Chemical Engineering Journal, 2024)

An approach based on a combination of toxicological experiments and in silico predictions to investigate the adverse outcome pathway (AOP) of paraquat neuro-immunotoxicity - Chunhui Zhang; Ge Shi; Qi Meng; Rong Hu; Yang Li; Guiling Hu; Kaidong Wang; Min Huang (Journal of Hazardous Materials, 2024)

Toxic mechanisms of nanoplastics exposure at environmental concentrations on juvenile red swamp crayfish (Procambarus clarkii): From multiple perspectives - Long Wang; Qianqian Zhu; Meng Hu; Xinyi Zhou; Tianyu Guan; Nan Wu; Chuankun Zhu; Hui Wang; Guiling Wang; Jiale Li (Environmental Pollution, 2024)

Soil water dynamics and deep percolation in an agricultural experimental area of the North China Plain over the past 50 years: Based on field monitoring and numerical modeling - Yanyan Wang; Yujiang He; Zhiping Li; Jihong Qu; Guiling Wang (Science of The Total Environment, 2024)

Ecological transitions in Xinjiang, China: Unraveling the impact of climate change on vegetation dynamics (1990–2020) - Haichao Hao; Junqiang Yao; Yaning Chen; Jianhua Xu; Zhi Li; Weili Duan; Sadaf Ismail; Guiling Wang (Journal of Geographical Sciences, 2024)

Focus on the nonlinear infiltration process in deep vadose zone - Yujiang He; Yanyan Wang; Ying Liu; Borui Peng; Guiling Wang (Earth-Science Reviews, 2024)

Absorption and utilization of polysaccharides from Cordyceps militaris fruiting bodies and their protective effects against CCl4-induced acute liver injury in mice - Lin Lan; Jingxin Wang; Hao Luo; Min Cao; Nianhong Guo; Guiling Fan; Shengyu Wang; Zaixing Sun; QiaoLing He; Yufeng Li (Food Bioscience, 2024)

Structure-activity relationships of antimicrobial phenolic derivatives from Phyllanthus emblica against Streptomyces scabies - Xiuna Wu; Daren Wu; Jiahao Yuan; Lingyu Zhang; Jingwen Liu; Guiling Li; Li Wang; Jian Li (Food Bioscience, 2024)

Defects engineering and interface regulation on nickel-rich sulphides promoting water/urea/ethanol electrooxidation - Xuan Zhang; Xianchao Wang; Qing Yan; Ruiqin Gao; Jing Zhao; Zichen Song; Kai Zhu; Dianxue Cao; Jiaxin Yao; Lingwei Zheng; Guiling Wang (Chemical Engineering Journal, 2024)

Regional climate model intercomparison over the Tibetan Plateau in the GEWEX/LS4P Phase I - Jianping Tang; Yongkang Xue; Mengyuan Long; Mengnan Ma; Xin-Zhong Liang; Shiori Sugimoto; Kun Yang; Zhenming Ji; Jinkyu Hong; Jeongwon Kim; Haoran Xu; Xu Zhou; et al. (Climate Dynamics, 2024)

Heritability Estimates for Growth Traits and Correlation Analysis between Weight and Metamorphosis Rate in the Bullfrog Rana (Aquarana) catesbeiana - Wencheng Xu; Yanzhe Wang; Guodong Wang; Lili Zhang; Guiling Zhang; Zhipeng Huo; Hui Ge (Fishes, 2024)
Metamorphosis is a crucial process in the life cycle of Rana (Aquarana) catesbeiana. R. catesbeiana tadpoles, in their short larval period, possess a high survival rate and also a highly competitive ability in the amphibious stage. In actual seed production, the economic traits of larval period and metamorphosis rate are used as quantifiable indicators of quality for individuals and populations, respectively. However, studies of these economic traits in larval cultivation and production are still lacking. In this study, we constructed 40 full-sib families of R. catesbeiana and measured the weight and metamorphosis rate of tadpoles at different developmental stages. Subsequently, we calculated the phenotypic and genetic association between weight and metamorphosis rate in tadpoles and assessed the heritability of these two traits. The heritabilities of weight at three developmental stages were all higher than 0.40 and decreased with advancement of the developmental stage; the heritability of the metamorphosis rate was 0.18 ± 0.20, a moderate level. Correlation analysis of weight and metamorphosis rate at each developmental stage in each tadpole family showed that weight at stages 25-I, 25-II, and 25-III was significantly correlated at the phenotypic level but non-significantly at the genetic level. The metamorphosis rate was only moderately associated with stage 25-III weight (0.38, p

Antibiotic resistance gene distribution in Shine Muscat grapes and health risk assessment of streptomycin residues in mice - Weitao Wang; Ting Luo; Yao Zhao; Xinyuan Yang; Dou Wang; Guiling Yang; Yuanxiang Jin (Journal of Hazardous Materials, 2024)

A review of cumulative risk assessment of multiple pesticide residues in food: Current status, approaches and future perspectives - Mengxue Yang; Yihan Wang; Guiling Yang; Yanhua Wang; Fengquan Liu; Chen Chen (Trends in Food Science & Technology, 2024)

Flash Joule heating induced highly defective graphene towards ultrahigh lithium ion storage - Shu Dong; Yali Song; Mingyu Su; Guiling Wang; Yingyi Gao; Kai Zhu; Dianxue Cao (Chemical Engineering Journal, 2024)

Coupled THMC modeling on chemical stimulation in fractured geothermal reservoirs - Haoran Xu; Guihong Liu; Zhihong Zhao; Feng Ma; Guiling Wang; Yuedu Chen (Geothermics, 2024)

The occurrence of typical psychotropic drugs in the aquatic environments and their potential toxicity to aquatic organisms - A review - Xianghai Zhu; Ting Luo; Dou Wang; Yao Zhao; Yuanxiang Jin; Guiling Yang (Science of The Total Environment, 2023)

Deep structure of the Rongcheng geothermal field, Xiongan New Area: Constraints from resistivity data and boreholes - Yunqi Zhu; Diquan Li; Yanfang Hu; Xian Zhang; Fu Li; Feng Ma; Guiling Wang (Geothermics, 2023)

Stress estimation in a 3 km-deep geothermal borehole: A snapshot of stress state in Southern Cathaysia block, China - Chongyuan Zhang; Bin Li; Hailong Li; Manchao He; Haonan Gan; Guiling Wang; Yanxia Fan (Tectonophysics, 2023)

De-carbonization and carbon utilization for subsurface energy transition: Introduction - Guodong Cui; Zhonghe Pang; Guiling Wang; Xiangzeng Wang; Bo Ren (Gondwana Research, 2023)

Heat source model for Enhanced Geothermal Systems (EGS) under different geological conditions in China - Wenjing Lin; Guiling Wang; Haonan Gan; Shengsheng Zhang; Zhen Zhao; Gaofan Yue; Xiting Long (Gondwana Research, 2023)

Study on the Role of Mitophagy Receptor PHB2 in Doubly Uniparental Inheritance of Hyriopsis cumingii - Yayu Wang; Xiaoyue Zhu; Yang Gu; Zongyu Liu; Yingrui Mao; Xiaojun Liu; Zhiyi Bai; Guiling Wang; Jiale Li (Marine Biotechnology, 2023)

Heat stress to jeopardize crop production in the US Corn Belt based on downscaled CMIP5 projections - Meijian Yang; Guiling Wang (Agricultural Systems, 2023)

Associations between environmental heavy metals exposure and preserved ratio impaired spirometry in the U.S. adults - Chen Chen; Shunan Zhang; Ting Yang; Chen Wang; Guiling Han (Environmental Science and Pollution Research, 2023)
We examined 9556 individuals aged 18 to 79 years who had information on spirometry testing and heavy metals and used multivariable logistic or linear regression to evaluate associations between serum levels of cadmium, lead, and mercury and PRISm and lung function in U.S. adults, which were conducted first in all participants, and then separately in never/former smokers and current smokers. The overall prevalence of PRISm was 7.02%. High levels of serum cadmium were significantly associated with PRISm in all individuals, no matter in never/former smokers (quartile 4 vs 1, the OR = 2.517, 95% CI = 1.376–4.604, p -trend = 0.0077) and current smokers (quartile 4 vs 1, the OR = 2.201, 95% CI = 1.265–3.830, p -trend = 0.0020). Serum lead and mercury were not significantly correlated with PRISm, regardless of smoking status. Serum cadmium was strongly correlated with lower FEV 1 /FVC, regardless of smoking status. Besides, serum cadmium was also significantly related to lower FVC % predicted in never/former smokers and lower FEV 1 % predicted in current smokers. Serum lead was strongly correlated with lower FVC % predicted and FEV 1 /FVC in all individuals and never/former smokers. And serum mercury was significantly associated with decrements in FVC % predicted in all individuals and current smokers. These findings demonstrate that serum cadmium is associated with a higher risk of PRISm and lower lung function, with the most significant effect on FEV 1 /FVC in particular. Our results also indicate that exposure to lead and mercury negatively affects lung function in never/former smokers and current smokers, respectively.

Cenozoic thermal-rheological evolution of the coastal cathaysia block of East Asia: geodynamic implications - Haonan Gan; Xiao Wang; Bo Wang; Guiling Wang (International Geology Review, 2023)

Urban rainfall-runoff flooding response for development activities in new urbanized areas based on a novel distributed coupled model - Donglai Li; Jingming Hou; Qingshi Zhou; Jiahao Lyu; Zhanpeng Pan; Tian Wang; Xueliang Sun; Guiling Yu; Junyan Tang (Urban Climate, 2023)

Water stress dominates the projected maize yield changes in Ethiopia - Meijian Yang; Guiling Wang; Ying Sun; Liangzhi You; Richard Anyah (Global and Planetary Change, 2023)

Effects of copper on gill function of juvenile oriental river prawn (Macrobrachium nipponense): Stress and toxic mechanism - Long Wang; Tianyu Guan; Guiling Wang; Jieyi Gu; Nan Wu; Chuankun Zhu; Hui Wang; Jiale Li (Aquatic Toxicology, 2023)

Influencing factors of rock thermal conductivity and applicability evaluation of its mixing law predictive models - Jiajia Song; Guiling Wang; Linxiao Xing; Jiazhong Qian; Lei Dai; He Di (Geothermics, 2023)

Geochemical processes and indicative significance of rare earth elements in high arsenic geothermal fluids in Batang, western Sichuan, China - wei Zhang; hanxiong Zhang; guiling Wang; jiayi Zhao; gaofan Yue; man Li; shuaichao Wei; zewei Qu (Geothermics, 2023)

Modulation of non-covalent wet adhesion and cohesion via proximally immobilized non-lysine pair structure - Pengxu Wang; Qing Liu; Wenliang Fu; Chao Zhang; Guiling Cai; Weiwei Xing; Hongliang Dai; Hongya Geng; Donggang Xu (Chemical Engineering Journal, 2023)

Breaking intramolecular hydrogen bonds of polymer films to enable dendrite-free and hydrogen-suppressed zinc metal anode - Yiyang Mao; Zhuo Li; Yiju Li; Dianxue Cao; Guiling Wang; Kai Zhu; Guohua Chen (Chemical Engineering Journal, 2023)

Seasonal prediction of crop yields in Ethiopia using an analog approach - Meijian Yang; Guiling Wang; Shu Wu; Paul Block; Rehenuma Lazin; Sarah Alexander; Jonathan Lala; Muhammad Rezaul Haider; Zoi Dokou; Ezana Amdework Atsbeha; Marika Koukoula; Xinyi Shen; et al. (Agricultural and Forest Meteorology, 2023)

Microwave-ultra-fast recovery of valuable metals from spent lithium-ion batteries by deep eutectic solvents - Ahui Zhu; Xinyu Bian; Weijiang Han; Yong Wen; Ke Ye; Guiling Wang; Jun Yan; Dianxue Cao; Kai Zhu; Shubin Wang (Waste Management, 2023)

Joint toxic effects of thiamethoxam and flusilazole on the adult worker honey bees (Apis mellifera L.) - Dou Wang; Lu Lv; Zhongwen Gao; Yu-Cheng Zhu; Hongbiao Weng; Guiling Yang; Yanhua Wang (Environmental Pollution, 2023)

Examining key impact factors of energy-related carbon emissions in 66 Belt and Road Initiative countries - Chuanhe Xiong; Guiling Wang; Hengpeng Li; Weizhong Su; Xuejun Duan (Environmental Science and Pollution Research, 2022)

G-CSF promotes the viability and angiogenesis of injured liver via direct effects on the liver cells - Zifeng Liu; Guiling Zhang; Jing Chen; Jingjing Tong; Hongmin Wang; Jing Chen; Dong Yang; Jinhua Hu (Molecular Biology Reports, 2022)
Background Presently, liver transplantation is the only treatment strategy for liver failure (LF). Although granulocyte-colony stimulating factor (G-CSF) exhibits protective functions in LF, it is not clear whether it directly affects the liver cells. Methods and Results We established an injured liver cell model and observed that G-CSF treatment promoted cell viability and enhanced Ki67 and VEGF-A expression. Thereafter, human umbilical vein endothelial cells (HUVECs) were cultured in a conditioned medium collected from the G-CSF-treated injured liver cells. HUVECs’ proliferation and tubule formation were promoted. Furthermore, in an injured liver mouse model, confirmed via haematoxylin–eosin staining, we evaluated serum alanine aminotransferase activity, Ki67 expression, and microvessel density (MVD). G-CSF treatment significantly relieved liver injury, upregulated Ki67 expression, and enhanced MVD in the injured mouse liver tissue. Additionally, AKT and ERK signal targets were explored, and it was demonstrated that the effects of G-CSF on injured liver cells were mediated through the AKT and ERK signalling pathways. Conclusions G-CSF promotes injured liver viability and angiogenesis by directly affecting injured liver cells via the AKT and ERK signalling pathways. These findings improve our understanding of the role of G-CSF in recovery from LF.

Coupled Thermo-Hydro-Mechanical Modeling on the Rongcheng Geothermal Field, China - Feng Ma; Guihong Liu; Zhihong Zhao; Haoran Xu; Guiling Wang (Rock Mechanics and Rock Engineering, 2022)

Environmental impact assessment of ground source heat pump system for heating and cooling: a case study in China - Yijie Zhai; Tianzuo Zhang; Xianfeng Tan; Guiling Wang; Longchen Duan; Qipeng Shi; Changxing Ji; Yueyang Bai; Xiaoxu Shen; Jia Meng; Jinglan Hong (The International Journal of Life Cycle Assessment, 2022)

Immunodominant membrane protein (Imp) promotes the transmission of wheat blue dwarf (WBD) phytoplasma by directly interacting with α-tubulin in leafhoppers - Lei Ding; Wenjing Lu; Yanjun Yang; Qinrong Zhong; Tong Zhou; Guiling Wang; Chengyan Song; Wendong Ma; Wei Chen; Yunfeng Wu (European Journal of Plant Pathology, 2022)

Selecting low-carbon technologies and measures for high agricultural carbon productivity in Taihu Lake Basin, China - Chuanhe Xiong; Guiling Wang; Weizhong Su; Qun Gao (Environmental Science and Pollution Research, 2021)

Assessing soil fractal and sorting characteristics based on geostatistics and modeling approaches in a typical basin of North China plain - Lei Dai; Guiling Wang; Yujiang He (Earth Science Informatics, 2021)

Using triple oxygen isotopes and oxygen-argon ratio to quantify ecosystem production in the mixed layer of northern South China Sea slope region - Zhuoyi Zhu; Jun Wang; Guiling Zhang; Sumei Liu; Shan Zheng; Xiaoxia Sun; Dongfeng Xu; Meng Zhou (Acta Oceanologica Sinica, 2021)

Flavonoids improve drought tolerance of maize seedlings by regulating the homeostasis of reactive oxygen species - Baozhu Li; Ruonan Fan; Guiling Sun; Ting Sun; Yanting Fan; Shenglong Bai; Siyi Guo; Shiquan Huang; Jiong Liu; Hui Zhang; Pengtao Wang; Xiaohong Zhu; et al. (Plant and Soil, 2021)
Background and aims As drought threatens the yield and quality of maize ( Zea mays L.), it is important to dissect the molecular basis of maize drought tolerance. Flavonoids, participate in the scavenging of oxygen free radicals and alleviate stress-induced oxidative damages. This study aims to dissect the function of flavonoids in the improvement of maize drought tolerance. Methods Using far-infrared imaging screening, we previously isolated a drought overly insensitivity ( doi ) mutant from an ethyl methanesulfonate (EMS)-mutagenized maize library and designated it as doi57 . In this study, we performed a physiological characterization and transcriptome profiling of doi57 in comparison to corresponding wild-type B73 under drought stress. Results Under drought stress, doi57 seedlings displayed lower leaf-surface temperature (LST), faster water loss, and better performance in growth than B73. Transcriptome analysis reveals that key genes involved in flavonoid biosynthesis are enriched among differentially expressed genes in doi57 . In line with these results, more flavonols and less hydrogen peroxide (H 2 O 2 ) were accumulated in guard cells of doi57 than in those of B73 with the decrease of soil water content (SWC). Moreover, the capacity determined from doi57 seedling extracts to scavenge oxygen free radicals was more effective than that of B73 under the drought treatment. Additionally, doi57 seedlings had higher photosynthetic rates, stomatal conductance, transpiration rates, and water use efficiency than B73 exposed to drought stress, resulting in high biomass and greater root/shoot ratios in doi57 mutant plants. Conclusion Flavonoids may facilitate maize seedling drought tolerance by lowering drought-induced oxidative damage as well regulating stomatal movement.

Transformation of coccolithophorid Emiliania huxleyi harboring a marine virus (Coccolithoviruses) serine palmitoyltransferase (SPT) gene by electroporation - Weicong Cai; Xueting Wang; Jinjing Su; Jian Li; Jun Zeng; Guiling Li; Jingwen Liu (Journal of Oceanology and Limnology, 2021)

Combined toxic impacts of thiamethoxam and four pesticides on the rare minnow (Gobiocypris rarus) - Guiling Yang; Lu Lv; Shanshan Di; Xinfang Li; Hongbiao Weng; Xinquan Wang; Yanhua Wang (Environmental Science and Pollution Research, 2021)

Toxicological interactions of cadmium and four pesticides on early life stage of rare minnow (Gobiocypris rarus) - Yanhua Wang; Xinfang Li; Chao Xu; Guiling Yang; Dou Wang; Xinquan Wang; Qiang Wang (Ecotoxicology, 2020)

Projecting the future vegetation–climate system over East Asia and its RCP-dependence - Weiguang Liu; Guiling Wang; Miao Yu; Haishan Chen; Yelin Jiang; Meijian Yang; Ying Shi (Climate Dynamics, 2020)

Projection of vegetation impacts on future droughts over West Africa using a coupled RegCM-CLM-CN-DV - Muhammad Shafqat Mehboob; Yeonjoo Kim; Jaehyeong Lee; Myoung-Jin Um; Amir Erfanian; Guiling Wang (Climatic Change, 2020)

Three Types of Spatial Function Zoning in Key Ecological Function Areas Based on Ecological and Economic Coordinated Development: A Case Study of Tacheng Basin, China - Guiling Wang; Degang Yang; Fuqiang Xia; Ruisen Zhong; Chuanhe Xiong (Chinese Geographical Science, 2019)

Quality Control and Evaluation of the Observed Daily Data in the North American Soil Moisture Database - Weilin Liao; Dagang Wang; Guiling Wang; Youlong Xia; Xiaoping Liu (Journal of Meteorological Research, 2019)

Identification of porcine CTLA4 gene polymorphism and their association with piglet diarrhea and performance traits - Xiaowen Gao; Dongchun Guo; Mingxing Kou; Guiling Xing; Andong Zha; Xiuqin Yang; Xibiao Wang; Shengwei Di; Jiancheng Cai; Buyue Niu (Molecular Biology Reports, 2019)

Role of resolution in regional climate change projections over China - Ying Shi; Guiling Wang; Xuejie Gao (Climate Dynamics, 2018)

Hydraulic redistribution affects modeled carbon cycling via soil microbial activity and suppressed fire - Congsheng Fu; Guiling Wang; Kenneth Bible; Michael L. Goulden; Scott R. Saleska; Russell L. Scott; Zoe G. Cardon (Global Change Biology, 2018)
Hydraulic redistribution (HR) of water from moist to drier soils, through plant roots, occurs world‐wide in seasonally dry ecosystems. Although the influence of HR on landscape hydrology and plant water use has been amply demonstrated, HR's effects on microbe‐controlled processes sensitive to soil moisture, including carbon and nutrient cycling at ecosystem scales, remain difficult to observe in the field and have not been integrated into a predictive framework. We incorporated a representation of HR into the Community Land Model (CLM4.5) and found the new model improved predictions of water, energy, and system‐scale carbon fluxes observed by eddy covariance at four seasonally dry yet ecologically diverse temperate and tropical AmeriFlux sites. Modeled plant productivity and microbial activities were differentially stimulated by upward HR, resulting at times in increased plant demand outstripping increased nutrient supply. Modeled plant productivity and microbial activities were diminished by downward HR. Overall, inclusion of HR tended to increase modeled annual ecosystem uptake of CO 2 (or reduce annual CO 2 release to the atmosphere). Moreover, engagement of CLM4.5′s ground‐truthed fire module indicated that though HR increased modeled fuel load at all four sites, upward HR also moistened surface soil and hydrated vegetation sufficiently to limit the modeled spread of dry season fire and concomitant very large CO 2 emissions to the atmosphere. Historically, fire has been a dominant ecological force in many seasonally dry ecosystems, and intensification of soil drought and altered precipitation regimes are expected for seasonally dry ecosystems in the future. HR may play an increasingly important role mitigating development of extreme soil water potential gradients and associated limitations on plant and soil microbial activities, and may inhibit the spread of fire in seasonally dry ecosystems.

Assessing simulated summer 10-m wind speed over China: influencing processes and sensitivities to land surface schemes - Xin-Min Zeng; Ming Wang; Ning Wang; Xiang Yi; Chaohui Chen; Zugang Zhou; Guiling Wang; Yiqun Zheng (Climate Dynamics, 2018)

Potential climate effect of mineral aerosols over West Africa: Part II—contribution of dust and land cover to future climate change - Zhenming Ji; Guiling Wang; Miao Yu; Jeremy S. Pal (Climate Dynamics, 2018)

Virus-induced apoptosis and phosphorylation form of metacaspase in the marine coccolithophorid Emiliania huxleyi - Jingwen Liu; Weicong Cai; Xian Fang; Xueting Wang; Guiling Li (Archives of Microbiology, 2018)

The dissipation and risk assessment of 2,4-D sodium, a preharvest anti-fruit-drop plant hormone in bayberries - Huiyu Zhao; Guiling Yang; Senmiao Liang; Qianbin Huang; Qiang Wang; Wanze Dai; Zhiheng Zhang; Wen Wang; Wen Song; Zheng Cai (Environmental Science and Pollution Research, 2017)

Influence of a water regulation event on the age of Yellow River water in the Bohai - Zhen Li; Haiyan Wang; Xinyu Guo; Zhe Liu; Huiwang Gao; Guiling Zhang (Journal of Ocean University of China, 2017)

A novel PTP1b inhibitor vanadium-flavone complex: synthesis and pharmacodynamic evaluation in streptozotocin-induced diabetic mice - Liying Duan; Junwei Ye; Wenlong Sun; Shaoning Wang; Wei-tao Gong; Yuesheng Dong; Guiling Ning (Medicinal Chemistry Research, 2017)

Estimated influence of urbanization on surface warming in Eastern China using time‐varying land use data - Weilin Liao; Dagang Wang; Xiaoping Liu; Guiling Wang; Jinbao Zhang (International Journal of Climatology, 2017)
We examine the urban effect on surface warming in Eastern China, where a substantial portion of the land area has undergone rapid urbanization in the last few decades. Daily surface air temperature records during the period 1971–2010 at 277 meteorological stations are used to investigate temperature changes. Owing to urban expansion, some of the stations formerly located in rural areas are becoming increasingly influenced by urban environments. To estimate the effect of this urbanization on observed surface warming, the stations are dynamically classified into urban and rural types based on the land use data for four periods, i.e. 1980, 1990, 2000 and 2010. After eliminating the temperature trend bias induced by time‐varying latitudinal distributions of urban and rural stations, the estimated urban‐induced trends in the daily minimum and mean temperature are 0.167 and 0.085 °C decade −1 , accounting for 33.6 and 22.4% of total surface warming, respectively. The temperature difference between urban and rural stations indicates that urban heat island intensity has dramatically increased owing to rapid urbanization, and is highly correlated with the difference in fractional coverage of artificial surfaces between these two types of stations. This study highlights the importance of dynamic station classification in estimating the contribution of urbanization to long‐term surface warming over large areas.

Combined toxicity of imidacloprid and three insecticides to the earthworm, Eisenia fetida (Annelida, Oligochaeta) - Tao Cang; Dejiang Dai; Guiling Yang; Yijun Yu; Lu Lv; Leiming Cai; Qiang Wang; Yanhua Wang (Environmental Science and Pollution Research, 2017)

Individual and mixture effects of five agricultural pesticides on zebrafish (Danio rerio) larvae - Yanhua Wang; Guiling Yang; Dejiang Dai; Zhenlan Xu; Leiming Cai; Qiang Wang; Yijun Yu (Environmental Science and Pollution Research, 2017)

The regional impact of Land-Use Land-cover Change (LULCC) over West Africa from an ensemble of global climate models under the auspices of the WAMME2 project - Aaron Anthony Boone; Yongkang Xue; Fernando De Sales; Ruth E. Comer; Samson Hagos; Sarith Mahanama; Kathleen Schiro; Guoqiong Song; Guiling Wang; S. Li; Carlos R. Mechoso (Climate Dynamics, 2016)

West African monsoon decadal variability and surface-related forcings: second West African Monsoon Modeling and Evaluation Project Experiment (WAMME II) - Yongkang Xue; Fernando De Sales; William K.-M. Lau; Aaron Boone; Kyu-Myong Kim; Carlos R. Mechoso; Guiling Wang; Fred Kucharski; Kathleen Schiro; Masahiro Hosaka; Suosuo Li; Leonard M. Druyan; et al. (Climate Dynamics, 2016)

Modeling the potential contribution of land cover changes to the late twentieth century Sahel drought using a regional climate model: impact of lateral boundary conditions - Guiling Wang; Miao Yu; Yongkang Xue (Climate Dynamics, 2016)

Effects of vegetation feedback on future climate change over West Africa - Miao Yu; Guiling Wang; Jeremy S. Pal (Climate Dynamics, 2016)

HO-1 Signaling Activation by Pterostilbene Treatment Attenuates Mitochondrial Oxidative Damage Induced by Cerebral Ischemia Reperfusion Injury - Yang Yang; Jiayi Wang; Yue Li; Chongxi Fan; Shuai Jiang; Lei Zhao; Shouyin Di; Zhenlong Xin; Bodong Wang; Guiling Wu; Xia Li; Zhiqing Li; et al. (Molecular Neurobiology, 2016)

Potential climate effect of mineral aerosols over West Africa. Part I: model validation and contemporary climate evaluation - Zhenming Ji; Guiling Wang; Jeremy S. Pal; Miao Yu (Climate Dynamics, 2016)

On the development of a coupled regional climate–vegetation model RCM–CLM–CN–DV and its validation in Tropical Africa - Guiling Wang; Miao Yu; Jeremy S. Pal; Rui Mei; Gordon B. Bonan; Samuel Levis; Peter E. Thornton (Climate Dynamics, 2016)

Impact of land cover characterization on regional climate modeling over West Africa - Mouhamadou Bamba Sylla; Jeremy S. Pal; Guiling L. Wang; Peter J. Lawrence (Climate Dynamics, 2016)

Potential impact of climate change on cereal crop yield in West Africa - Kazi Farzan Ahmed; Guiling Wang; Miao Yu; Jawoo Koo; Liangzhi You (Climatic Change, 2015)

Activation of endoplasmic reticulum stress is involved in the activity of icariin against human lung adenocarcinoma cells - Shouyin Di; Chongxi Fan; Yang Yang; Shuai Jiang; Miaomiao Liang; Guiling Wu; Bodong Wang; Zhenlong Xin; Wei Hu; Yifang Zhu; Weimiao Li; Yongan Zhou; et al. (Apoptosis, 2015)

Joint toxicity of chlorpyrifos, atrazine, and cadmium at lethal concentrations to the earthworm Eisenia fetida - Guiling Yang; Chen Chen; Yanhua Wang; Leiming Cai; Xiangzhen Kong; Yongzhong Qian; Qiang Wang (Environmental Science and Pollution Research, 2015)

Quantifying the preferential flow by dye tracer in the North China Plain - Qinghua Wu; Chunlei Liu; Wenjing Lin; Meng Zhang; Guiling Wang; Fawang Zhang (Journal of Earth Science, 2015)

Impact of climate change on hydrological extremes in the Yangtze River Basin, China - Huanghe Gu; Zhongbo Yu; Guiling Wang; Jigan Wang; Qin Ju; Chuanguo Yang; Chuanhao Fan (Stochastic Environmental Research and Risk Assessment, 2015)

Bayesian Markov Chain Random Field Cosimulation for Improving Land Cover Classification Accuracy - Weidong Li; Chuanrong Zhang; Michael R. Willig; Dipak K. Dey; Guiling Wang; Liangzhi You (Mathematical Geosciences, 2015)

Health risk assessment of Chinese consumers to nickel via dietary intake of foodstuffs - Wen Wang; Zhiheng Zhang; Guiling Yang; Qiang Wang (Food Additives & Contaminants: Part A, 2014)

Future changes of the terrestrial ecosystem based on a dynamic vegetation model driven with RCP8.5 climate projections from 19 GCMs - Miao Yu; Guiling Wang; Dana Parr; Kazi Farzan Ahmed (Climatic Change, 2014)

Large-scale analysis of protein phosphorylation in Populus leaves - Jinwen Liu; Deli Ning; Guiling Zhao; Yuxiang Cheng; Baichen Wang (Journal of Plant Biochemistry and Biotechnology, 2014)

Comparative analysis of total carotenoid content in tissues of purple and white inner-shell color pearl mussel, Hyriopsis cumingii - Xilei Li; Zhiyi Bai; Hongrui Luo; Guiling Wang; Jiale Li (Aquaculture International, 2014)

Identification of housekeeping genes suitable for gene expression analysis in the pearl mussel, Hyriopsis cumingii, during biomineralization - Zhiyi Bai; Jingyun Lin; Keyi Ma; Guiling Wang; Donghong Niu; Jiale Li (Molecular Genetics and Genomics, 2014)

Role of the Indian Ocean sea surface temperature in shaping the natural variability in the flow of Nile River - Mohamed S. Siam; Guiling Wang; Marie-Estelle Demory; Elfatih A. B. Eltahir (Climate Dynamics, 2014)

Impacts of bias correction of lateral boundary conditions on regional climate projections in West Africa - Miao Yu; Guiling Wang (Climate Dynamics, 2014)

Climate variability attributable to terrestrial and oceanic forcing in the NCAR CAM3-CLM3 Models - Shanshan Sun; Guiling Wang (Climate Dynamics, 2014)

A new insect cell line from the pupal ovary of the Asian corn borer moth Ostrinia furnacalis - Ning Zhang; Qilian Qin; Huan Gong; Qian Meng; Wei Zhu; Menglong Wang; Jihong Zhang; Guiling Zhou; Xuan Li; Huan Zhang (In Vitro Cellular & Developmental Biology - Animal, 2014)

Identification of QTLs for salt tolerance at germination and seedling stage of Sorghum bicolor L. Moench - Hailian Wang; Guiling Chen; Huawen Zhang; Bin Liu; Yanbing Yang; Ling Qin; Erying Chen; Yanan Guan (Euphytica, 2014)

Comparison of growth and pearl production in males and females of the freshwater mussel, Hyriopsis cumingii, in China - Yongchao Zhao; Zhiyi Bai; Longlong Fu; Yue Liu; Guiling Wang; Jiale Li (Aquaculture International, 2013)

Mechanisms of summertime precipitation variability in the Bolivian Altiplano: present and future - Jeanne Thibeault; Anji Seth; Guiling Wang (International Journal of Climatology, 2012)
Water availability is a major constraint to rural agriculture in the Bolivian Altiplano. The ability of medium and high‐resolution CMIP3 models to simulate observed relationships between interannual Altiplano summer precipitation anomalies and large‐scale patterns of precipitation, 200‐hPa winds and 200‐hPa geopotential height is examined. Altiplano precipitation anomalies are known to be related to upper‐level wind anomalies, with westerly (easterly) anomalies associated with deficit (excess) rainfall. A majority of models are able to simulate an easterly/wet‐westerly/dry relationship in response to changes in the zonal flow produced by fluctuations in tropical tropospheric temperatures that affect the meridional temperature gradient, consistent with observations. The 21st century evolution of these relationships under conditions of greenhouse warming is also examined. Results indicate that wet anomalies will continue to require moisture transport from the east. However, expected changes in mean circulation (e.g. tropical tropospheric warming) will likely influence precipitation variability. Models that better simulate Altiplano precipitation variability project an increase in 200‐hPa westerly winds by 2050–2099, which are not favourable for precipitation in the Altiplano. The reduced frequency of summertime upper‐level easterly wind anomalies may explain projections for less frequent summertime rainfall. Models that better simulate Altiplano precipitation variability project reduced summertime precipitation, consistent with projections for more frequent westerly wind anomalies. Summertime soil moisture reductions are expected from about 2020 onward due to reductions in summer rainfall, increases in the runoff ratio, higher evapotranspiration rates, and reduced precipitation frequency. These findings are consistent with expected large‐scale changes in atmospheric circulation, providing confidence in the projections. These results have serious implications for water resources and food security in the Altiplano, but will require further testing with improved, higher‐resolution models. Copyright © 2011 Royal Meteorological Society

Programmed cell death is responsible for replaceable bud senescence in chestnut (Castanea mollissima BL.) - Guangpeng Wang; Zhihong Zhang; Dejun Kong; Qingxiang Liu; Guiling Zhao (Plant Cell Reports, 2012)

Assessing future climate changes and extreme indicators in east and south Asia using the RegCM4 regional climate model - Huanghe Gu; Guiling Wang; Zhongbo Yu; Rui Mei (Climatic Change, 2012)

Molecular cytogenetic identification of a novel dwarf wheat line with introgressed Thinopyrum ponticum chromatin - Guiling Chen; Qi Zheng; Yinguang Bao; Shubing Liu; Honggang Wang; Xingfeng Li (Journal of Biosciences, 2012)

Integrating miRNA and mRNA expression profiles in response to heat stress-induced injury in rat small intestine - Jin Yu; Fenghua Liu; Peng Yin; Xiaoyu Zhu; Guiling Cheng; Nin Wang; An Lu; Weili Luan; Nuowei Zhang; Jiefeng Li; Kaijun Guo; Yulong Yin; et al. (Functional & Integrative Genomics, 2011)

Droughts, hydraulic redistribution, and their impact on vegetation composition in the Amazon forest - Guiling Wang; Clement Alo; Rui Mei; Shanshan Sun (Plant Ecology, 2011)

Role of dynamic vegetation in regional climate predictions over western Africa - Clement Aga Alo; Guiling Wang (Climate Dynamics, 2010)

Analysis on cDNA sequence, mRNA expression and imprinting status of Dlk1 gene in goats - Guiling Cao; Yujie Zhang; Jianmin Wang; Yunliang Jiang (Molecular Biology Reports, 2010)

Rain follows logging in the Amazon? Results from CAM3–CLM3 - Rui Mei; Guiling Wang (Climate Dynamics, 2010)

Identification of Genes Involved in Immune Response, Microsatellite, and SNP Markers from Expressed Sequence Tags Generated from Hemocytes of Freshwater Pearl Mussel (Hyriopsis cumingii) - Zhiyi Bai; Yuxin Yin; Songnian Hu; Guiling Wang; Xiaowei Zhang; Jiale Li (Marine Biotechnology, 2009)

Response of isoprene emission to ambient CO 2 changes and implications for global budgets - COLETTE L. HEALD; MICHAEL J. WILKINSON; RUSSELL K. MONSON; CLEMENT A. ALO; GUILING WANG; ALEX GUENTHER (Global Change Biology, 2009)
We explore the potential role of atmospheric carbon dioxide (CO 2 ) on isoprene emissions using a global coupled land–atmosphere model [Community Atmospheric Model–Community Land Model (CAM–CLM)] for recent (year 2000, 365 ppm CO 2 ) and future (year 2100, 717 ppm CO 2 ) conditions. We incorporate an empirical model of observed isoprene emissions response to both ambient CO 2 concentrations in the long‐term growth environment and short‐term changes in intercellular CO 2 concentrations into the MEGAN biogenic emission model embedded within the CLM. Accounting for CO 2 inhibition has little impact on predictions of present‐day global isoprene emission (increase from 508 to 523 Tg C yr −1 ). However, the large increases in future isoprene emissions typically predicted in models, which are due to a projected warmer climate, are entirely offset by including the CO 2 effects. Projected global isoprene emissions in 2100 drop from 696 to 479 Tg C yr −1 when this effect is included, maintaining future isoprene sources at levels similar to present day. The isoprene emission response to CO 2 is dominated by the long‐term growth environment effect, with modulations of 10% or less due to the variability in intercellular CO 2 concentration. As a result, perturbations to isoprene emissions associated with changes in ambient CO 2 are largely aseasonal, with little diurnal variability. Future isoprene emissions increase by more than a factor of two in 2100 (to 1242 Tg C yr −1 ) when projected changes in vegetation distribution and leaf area density are included. Changing land cover and the role of nutrient limitation on CO 2 fertilization therefore remain the largest source of uncertainty in isoprene emission prediction. Although future projections suggest a compensatory balance between the effects of temperature and CO 2 on isoprene emission, the enhancement of isoprene emission due to lower ambient CO 2 concentrations did not compensate for the effect of cooler temperatures over the last 400 thousand years of the geologic record (including the Last Glacial Maximum).

Impact of sub-grid variability of precipitation and canopy water storage on hydrological processes in a coupled land–atmosphere model - Dagang Wang; Guiling Wang; Emmanouil N. Anagnostou (Climate Dynamics, 2009)

Agricultural drought in a future climate: results from 15 global climate models participating in the IPCC 4th assessment - Guiling Wang (Climate Dynamics, 2005)

Regime Shifts in the Sahara and Sahel: Interactions between Ecological and Climatic Systems in Northern Africa - Jonathan A. Foley; Michael T. Coe; Marten Scheffer; Guiling Wang (Ecosystems, 2003)

Reassessing the impact of North Atlantic Oscillation on the sub‐Saharan vegetation productivity - GUILING WANG (Global Change Biology, 2003)
The Northern Atlantic Oscillation (NAO) has been shown to have a significant impact on the terrestrial ecosystem in the Sahelian region of Africa during the 1980s, and it has been strongly suggested that NAO may be a reliable predictor for the response of the Sahelian ecosystem to global climate variability. Using data from an extended period, we provide a reassessment for the impact of NAO on the Sahelian climate and ecosystem, and show that there is no consistent relationship between NAO and the ecosystem over Sahel. Statistical analysis on the NAO, vegetation, and precipitation data indicates that NAO influences the Sahelian vegetation productivity exclusively through its impact on precipitation. However, the relationship between the NAO index and Sahelian precipitation varies substantially with time. The correlation coefficient fluctuates between positive and negative values, and does not pass the 5% significance test during most of the twentieth century. The NAO system, although documented to govern the ecosystem dynamics over many other regions, does not have a consistent impact on the ecosystem over the Sahel. Therefore, the NAO index cannot produce a useful prediction on the ecosystem variability and changes in this region. This study provides an example that correlations based on short climate and ecological records (less than 20 years in this case) can be spurious and potentially misleading.

Impact of CO 2 concentration changes on the biosphere‐atmosphere system of West Africa - GUILING WANG; ELFATIH A. B. ELTAHIR (Global Change Biology, 2002)
Vegetation dynamics plays a critical role in causing the decadal variability of precipitation over the Sahel region of West Africa. However, the potential impact of changes in CO 2 concentration on vegetation dynamics and precipitation variability of this region has not been addressed by previous studies. In this paper, we explore the role of CO 2 concentration in the regional climate system of West Africa using a zonally symmetric, synchronously coupled biosphere‐atmosphere model. We first document the response of precipitation and vegetation to incremental changes of CO 2 concentration; the impact of CO 2 concentration on the variability of the regional biosphere‐atmosphere system is then addressed using the second half of the twentieth century as an example. An increase of CO 2 concentration causes the regional biosphere‐atmosphere system to become wetter and greener, with the radiative effect of CO 2 and improved plant‐water relation dominant in the Sahelian grassland region and the direct enhancement of leaf carbon assimilation dominant in the tree‐covered region to the south. Driven by the observed sea surface temperature (SST) of the tropical Atlantic Ocean during the period 1950–97 and with CO 2 concentration prescribed at a pre‐industrial level 300ppmv, the model simulates a persistent Sahel drought during the period of 1960s−1990s. The simulated drought takes place in the form of a transition of the coupled biosphere‐atmosphere system from a wet/green regime in the 1950s to a dry/barren regime after the 1960s. This climate transition is triggered by SST forcing and materialized through vegetation‐climate interactions. The same SST forcing does not produce such a persistent drought when a constant modern CO 2 concentration of 350ppmv is specified, indicating that the biosphere‐atmosphere system at higher CO 2 level is more resilient to drought‐inducing external forcings. This finding suggests that the regional climate in Sahel, which tends to alternate between dry and wet spells, may experience longer (or more frequent) wet episodes and shorter (or less frequent) dry episodes in the future than in the past. Our study has significant implications regarding the impact of climate change on regional socio‐economic development.